IDENTIFICATION WATER LEVEL MONITORING SYSTEM AND PERSON DETECTION IN BATHROOM USING IOT CONNET APPLICATION - Muliadi Muliadi (Jurusan Pendidikan Teknik Elektro, 2024)
This Uncontrolled and excessive use of water can lead to the scarcity of clean water supplies, considering that the world's fresh water supply is only about 3%. An example of uncontrolled water use is when a tap user forgets to close the tap so this causes water waste. Therefore, a tool is needed that can solve these problems. This research aims to develop an IoT-based system that is able to monitor water levels and detect the presence of a person in the bathroom automatically to reduce water waste and increase user comfort. The system utilizes HC-SR04 ultrasonic sensors to measure the water level in the bathtub and PIR sensors to detect motion as an indicator of the presence of people. The data from the sensors is processed by the ESP32 microcontroller and forwarded to the IoT Connect application, which allows users to monitor the water volume and presence in the bathroom in real-time. The system also features a solenoid valve that automatically opens and closes the water flow according to the data from the sensor, as well as an LED as a visual indicator. Test results show that the system is able to accurately monitor water levels and detect the presence of a person, as well as provide automatic control of water flow to prevent wastage. With the integration of the IoT Connect app, the system offers a practical and innovative solution for bathroom water management.